Relevance of fatty acid covalently bound to Escherichia coli α-hemolysin and membrane microdomains in the oligomerization process - Herlax, Vanesa Silvana (2009)
α-Hemolysin (HlyA) is an exotoxin secreted by some pathogenic strains of Escherichia coli that causes lysis of several mammalian cells, including erythrocytes of different species. HlyA is synthesized as a protoxin, pro-HlyA, which is activated by acylation at two internal lysines Lys-563 and Lys-689. It has been proposed that pore formation is the mechanism of cytolytic activity for this toxin, as shown in experiments with whole cells, planar lipid membranes, and liposomes, but these experiments have yielded conflicting results about the structure of the pore. In this study, HlyA cysteine replacement mutant proteins of amino acids have been labeled with Alexa-488 and Alexa-546. Fluorescence resonance energy transfer measurements, employing labeled toxin bound to sheep ghost erythrocytes, have demonstrated that HlyA oligomerizes on erythrocyte membranes. As the cytotoxic activity is absolutely dependent on acylation, we have studied the role of acylation in the oligomerization, demonstrating that fatty acids are essential in this process. On the other hand, fluorescence resonance energy transfer and the hemolytic activity decrease when the erythrocyte ghosts are cholesterol-depleted, hence indicating the role of membrane microdomains in the clustering of HlyA. Simultaneously, HlyA was found in detergent-resistant membranes. Pro-HlyA has also been found in detergent-resistant membranes, thus demonstrating that the importance of acyl chains in toxin oligomerization is the promotion of protein-protein interaction. These results change the concept of the main role assigned to acyl chain in the targeting of proteins to membrane microdomains.